Indian J Pharm Sci 2020
DOI: 10.36468/pharmaceutical-sciences.674
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Purple Waxy Corn on Aflatoxin B1-induced Oxidative Stress and Micronucleus in HepG2 Cells

Abstract: The purpose of this study was to investigate the protective effects of purple waxy corn extract (Zea may L.) on aflatoxin B1-induced cytotoxicity, oxidative stress and micronuclei in HepG2 cells. Purple waxy corn extract contained phenolics (187.15-341.65 µg gallic acid/mg), flavonoids (0.55-21.35 µg quercetin/ mg) and anthocyanins (43.70-220.43 mg cyanidin-3-glucoside/l). Antioxidant activities of the extracts were measured using oxygen radical absorbance capacity (1410.70-2214.49 µM trolox/mg) and ferric red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…There was no significant difference in cell viability among the tested purple waxy corn concentrations (125 to 1,000 µg/mL), which is consistent with a previous study that reported that purple waxy corn at 3,000 µg/mL reduced Hep G2 cell viability to 60%. 23 Hence, the study continued using these concentrations. For ROS analysis, the DCFH-DA method was employed based on the reaction of ROS with DCFH-DA to create highly fluorescent dichlorofluorescein.…”
Section: Effects Of Purple Waxy Corn On Cell Viability Ros Ast and Altmentioning
confidence: 99%
“…There was no significant difference in cell viability among the tested purple waxy corn concentrations (125 to 1,000 µg/mL), which is consistent with a previous study that reported that purple waxy corn at 3,000 µg/mL reduced Hep G2 cell viability to 60%. 23 Hence, the study continued using these concentrations. For ROS analysis, the DCFH-DA method was employed based on the reaction of ROS with DCFH-DA to create highly fluorescent dichlorofluorescein.…”
Section: Effects Of Purple Waxy Corn On Cell Viability Ros Ast and Altmentioning
confidence: 99%
“…Such toxicity could be induced by the loss of mitochondrial function creating a mitochondrial metabolic gridlock, such as the inhibition of mitochondrial respiration (Prakash et al 2022). The in vitro hepatotoxicity of AFB1 and FB1 has been reported in many studies using the HepG2 cells as the preferred liver model (Abdul and Chuturgoon 2021; Chen et al 2022; Singto et al 2020). Oxidative stress, inflammation, and mitochondrial dysfunction by targeting ROS, DNA, p53, and other signaling pathways have been documented as toxic mechanism of AFB1 (Li et al 2022).…”
Section: Introductionmentioning
confidence: 99%